Studies on aspects of Autonomic Neuropathy in non Insulin dependent Diabetes - Levitt, Naomi Sharlene; Levitt, Naomi Sharlene (Division of Endocrinology and Diabetology, 2017)
Autonomic neuropathy (AN) is a well-recognized complication of diabetes mellitus. It has multiple clinical features and is often associated with debilitation and an increased mortality. However, there appears to be a paucity of knowledge with regard to its effects on hormone release and its biochemical sequelae. Recent evidence has accumulated suggesting a role for the autonomic nervous system in regulating release of a number of gastrointestinal hormones. It is therefore possible that autonomic dysfunction may be associated with altered gastrointestinal hormone release and indeed various studies have revealed abnormalities in t he release of these peptides in diabetes mellitus. The prime purpose of this thesis was to provide evidence which might contribute to an understanding of t he interrel a tionship between non insulin dependent diabetes (NIDDM), gastrointestinal hormone release and the autonomic nervous system. Thus studies to evaluate basal and stimulated release of the gastrointestinal hormones gluc a gon (IRG), pancreatic polypeptide (PP), gastrin, gastric inhibitory polypeptide (GIP) and somatostatin (SRIF-LI) have been undertaken in NIDDM. Studies were also carried out to assess whether AN may be implicated in abnormal release of these five gut hormones in diabetes and to determine if one of the hormones, PP, might be used as a marker for AN. Finally the effect of dietary fibre on glucose tolerance was studied to assess whether its effect would be altered in the presence of AN in NIDDM.